Analisis Determinan Volatilitas Saham Pada Jakarta Islamic Index (JII) - Farhadi Arifiansyah (Jurnal Ekonomi Syariah Pelita Bangsa, 2025)
The purpose of this study is to analyze the effect of dividend policy, leverage, asset growth, price-earnings ratio, and inflation on stock price volatility in Jakarta Islamic Index (JII) companies for the 2021-2024 period. The quantitative descriptive-causal research method used purposive sampling with a population of 30 and a sample of 18 consistent JII stocks. Secondary data were analyzed using multiple linear regression (Stata 14) after classical assumption testing. The dependent variables were independent volatility: Dividends, DER, asset growth, PER, and inflation. The results of this study are dividends (β=0.000456; *p*=0.010) and PER (β=0.0122; *p*=0.009) increase volatility significantly, while Leverage (β=-0.059; *p*=0.827), asset growth (β=0.0027; *p*=0.826), and inflation (β=0.0053; *p*=0.982) are not significant with a limited explanatory power of the model R²=16.57% the rest is explained by other variables outside the study.